2019
DOI: 10.1111/pan.13640
|View full text |Cite
|
Sign up to set email alerts
|

Airway management in patients with mucopolysaccharidoses: The progression toward difficult intubation

Abstract: Background:Patients with mucopolysaccharidoses (MPS) have physical changes to their airways over time. Due to the natural progression of their disease, these patients become more difficult to intubate as they get older. Aims:The aims of this study were to evaluate the difficulty of airway management in MPS patients over time, and to evaluate the effect of bone marrow transplant and/or enzyme replacement therapy on airway difficulty. Methods: A retrospective review of MPS patients presenting for surgery fromJan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 22 publications
(38 reference statements)
0
20
1
1
Order By: Relevance
“…In nonsyndromic children, the risk for perioperative critical events decreases with age . However, it has been proposed that due to disease progression during the natural history of MPS, the risk for intubation problems might paradoxically increase . Nevertheless, after adjustment for multiple confounders, we found that perioperative adverse events did not increase with age in our multivariate analysis.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…In nonsyndromic children, the risk for perioperative critical events decreases with age . However, it has been proposed that due to disease progression during the natural history of MPS, the risk for intubation problems might paradoxically increase . Nevertheless, after adjustment for multiple confounders, we found that perioperative adverse events did not increase with age in our multivariate analysis.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous case series addressed the issue of airway techniques in MPS, but did not provide direct comparative assessments taking essential confounding factors into account …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations